Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Aplikasi Canva untuk Meningkatkan Keterampilan Menulis Teks Prosedur Siswa Kelas VII SMP Swasta Tiara Bandar Setia - Putri Putri; Tri Indah Kusumawati; Budiman Budiman (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This research is entitled “Development of Student Worksheets (LKPD) Based on the Canva Application to Improve Procedure Text Writing Skills of Grade VII Students at Tiara Private Junior High School, Bandar Setia.” The background of this study is the low ability of students to write procedure texts, which is caused by the limited use of attractive and interactive learning media. To address this issue, the study developed a Canva-based LKPD designed to enhance students’ writing skills. The research method employed was Research and Development (R&D) using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research instruments included validation sheets for material experts, language experts, and media experts, as well as questionnaires to gather responses from teachers and students. The validation results indicate that the Canva-based LKPD is highly feasible for use in learning, with a material expert validation score of 96.36%, language expert 87%, media expert 87%, teacher response 94%, and student response 92%. Furthermore, implementation results demonstrated a significant improvement in students’ ability to write procedure texts, as evidenced by an increase in average scores from pretest to posttest. These findings suggest that the Canva-based LKPD is an effective and innovative learning medium that can facilitate students in improving their writing skills, particularly in learning procedure texts in Indonesian language classes. This research also contributes to the development of creative digital media for education in the current technological era.